Influence of garden structure and surrounding landscape on the presence of wildlife in Umeå - Andersson, Amanda (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2021)
Around the world cities are growing. Expansion and densification often take place at the expense of urban greenspace, the most common habitat for urban wildlife. Even though gardens take up a significant amount of the city's green space, there are no general guidelines on how to manage garden to support local wildlife. Increased knowledge about habitat selection of wildlife in gardens is therefore needed, to improve the management of these spaces to support local wildlife. In this study, I used a mixed method approach with a survey and camera trapping on 145 locations in Umeå, Northern Sweden. To improve our understanding on how wildlife uses gardens, I tested three hypotheses for six wildlife species using a generalized linear mixed model. I expected that gardens containing wildlife friendly features would have a higher wildlife visitation frequency, and my results showed a positive correlation for red fox. I also assumed that gardens with a more natural vegetation structure would have a higher wildlife visitation frequency, which I didn't find support for. I also expected that the wildlife visitation frequency would increase with natural habitat in the surrounding. My results showed the opposite, where the visits of red fox and magpies were less frequent if there was natural habitat existing in the surroundings.